2022
DOI: 10.3390/jpm12101612
|View full text |Cite
|
Sign up to set email alerts
|

Does the Timing of the Surgery Have a Major Role in Influencing the Outcome in Elders with Acute Subdural Hematomas?

Abstract: Background: The incidence of traumatic acute subdural hematomas (ASDH) in the elderly is increasing. Despite surgical evacuation, these patients have poor survival and low rate of functional outcome, and surgical timing plays no clear role as a predictor. We investigated whether the timing of surgery had a major role in influencing the outcome in these patients. Methods: We retrospectively retrieved clinical and radiological data of all patients ≥70 years operated on for post-traumatic ASDH in a 3 year period … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…1 ). 2 7 16 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 In the 42 articles within the quantitative analysis, 34 articles included patients operated on for ASDH, 2 16 24 25 26 27 30 31 33 34 35 37 38 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 ). 2 7 16 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 In the 42 articles within the quantitative analysis, 34 articles included patients operated on for ASDH, 2 16 24 25 26 27 30 31 33 34 35 37 38 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen point six percent (6/41) of the studies, accounting for 523 patients, reported radiologic factors influencing the functional outcome of patients suffering from ASDH. 7,54,56,[58][59][60] Midline shift appeared as the sole factor considered to be significantly associated with functional outcome (significant n ¼ 349, p ¼ 0.038; nonsignificant n ¼ 112). Brain contusion was considered to be possibly associated with functional outcome (significant n ¼ 62, p ¼ 0.037; nonsignificant n ¼ 213).…”
Section: Radiologic Factors Influencing Functional Outcome In the Eld...mentioning
confidence: 98%
See 3 more Smart Citations